IoT Helmet: an intelligent helmet for locating accidented bikers - Silva, Kleython da; Sabino, Márcio; Silva, Eliandro da; Gallegos, Luciano (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Every year, approximately 1,25 million people die in automobilistic accidents worldwide, where 23% are motorcyclists. Amongst the countries that have large motorcycle market, Brazil stands out between the largest ones comprising 22 million motorcycles and 30 million motorcyclists, where these machines are often used in remote or limited access locations such as on fields, dirt roads or isolated streets. In an motorcycle accident, it is common that the motorcyclist loose his consciousness and thus be unable to request help within the so-called 60 minutes "Golden Hour" limit. Considering the evolution and cheapeness of Internet of Things (IoT) technologies, applications aimed at saving lives become more and more common, making it easier to connect equipments in a data communication network. In this article, we describe a intelligent helmet equipped with embedded IoT technologies for geolocating and communicating with computer devices such as personal computers and mobile phone about accidented motorcyclists within 60 minutes in real-time. Simulations and tests shown promising results in real experiments where technologies such as sensors, microprocessor and the communication devices embedded in the IoT helmet's enable data colection and processing about the motorcyclist's situation, as well as wireless data transmisson and notification about his current status.